Unraveling the enigma of preterm birth: maternal factors, interventions, and neonatal implications - Thakkar, Chhalak Mukundchandra; Kapadia, Lalit D.; Patel, Arti J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Preterm birth is a substantial global health issue with significant consequences to the newborn, family and society. Preterm deliveries affects nearly 15 million births worldwide. Methods: A retrospective cross-sectional study, conducted in a tertiary healthcare center on 100 preterm births. The data used, was of a period of 6 months in 2023. Results: The incidence of preterm was found to be 100 out of 791 live births (12.4%). Among which majority, (64%), fell into the moderate to late preterm range and with 40% falling within the 21-25 age group .While 41% had less than four antenatal care visits. Among the identified risk factors in the preterm births, high blood pressure and anemia were prevalent medical disorders, affecting 20 and 36 of cases, respectively. In obstetrical factors, 24 were attributed to multiple gestations. Lower socioeconomic status was a significant contributing factor, affecting 55 of the studied population. NICU admission ranged from short stays of 1-3 days (34%) to more extended durations, with 18% requiring care for 10-21 days and tocolytics were employed in 27 cases, with a notable 66.60% instances demonstrating effectiveness in preventing preterm birth. Conclusions: In this study, we found high incidence of preterm birth (12.4%). Various socio-demographic, obstetric and neonatal risk factors were associated with preterm birth. Risk factor anticipation and timely interventions will help in the reduction of preterm births and associated mortalities.